From Rockfall Observation to Operational Solutions: Nearly 20 years of Cryo-gravitational Hazard Studies in Mont-Blanc Massif - Florence Magnin; Ludovic Ravanel; Matan Ben-Asher; Josué Bock; Maëva Cathala; Pierre-Allain Duvillard; Pierrick Jean; Jean-Yves Josnin; Suvrat Kaushik; André Revil; Philip Deline (Revue de Géographie Alpine)
The enhanced rockfall frequency (V > 100 m3) first noticed in the European Alps, has motivated investigations on high mountain rock walls and rock wall permafrost since the 2000s. Mont-Blanc massif (MBM) has become a pilot study area thanks to the wealth of data and knowledge on rockfall and permafrost dynamics acquired through successive research projects. Statistical analysis of rockfall distribution (> 1300 events inventoried between 2007 and 2021) shows that they are related to permafrost distribution and increasing atmospheric temperature, opening promising perspective for developing forecasting tools to support mountain practitioners in their risk mitigation strategy. However, understanding how rock wall destabilizations develop is challenged by the variety of potentially involved thermo-hydro-mechanical processes. To face these challenges, research currently carried out in the MBM focuses on water infiltration and circulation processes in frozen rock walls by combining advanced numerical modelling approaches and ad hoc field surveys. The coupling of models simulating heat and water transport with geoelectrical imaging methods could allow assessment of ground water/ice distributions and contents that is highly relevant for geotechnical purposes. Concurrently, the combination of acquired data and knowledge in integrative approaches of landscape changes and hazards involving permafrost degradation, glacier retreat, possible lake formation and rock wall destabilization appears as an essential basis for land-planning concerns. Finally, thermal and hydrological interactions between rock wall permafrost and ice bodies nestled on rock faces (ice aprons and hanging glaciers) is another direction of research to be pursued with cross-disciplinary implications.